Sucrose-delaying flower color fading associated with delaying anthocyanin accumulation decrease in cut chrysanthemum - Xiao-fen Liu; Ruping Teng; Lili Xiang; Fang Li; Kunsong Chen (PeerJ, 2023)
As fresh ornamental crops, vase life and post-harvested quality of cut flowers have attracted much attention. Flower color fading is the prominent defect in red and purple cut flowers, especially in cut chrysanthemum which have a relative long vase life. Here, the effect of sucrose on change in anthocyanin contents during the vase life of ‘Dante Purple’ cut chrysanthemum was studied. Results showed that 500 mM sucrose as holding solution could significantly delay the decrease in anthocyanin content and maintain the ornamental value for as long as 38 vase days. Moreover, the sucrose also increased the flower diameter, soluble sugar contents and total antioxidant capacity, while decreasing the malondialdehyde contents. Further studies suggested that the transcript levels of anthocyanin biosynthetic genes and transcription factors, CmMYB6 and CmMYB#7, had continuously decreased during the vase life. The changes in these genes expression patterns was retarded by the sucrose treatment, except for CmMYB#7 which is a repressor of anthocyanin biosynthesis gene expression. The decline in relative expression of CmMYB#7 was accelerated by sucrose. These results have supplied clues to study the mechanism whereby sucrose serves as a signal molecule to regulate anthocyanin biosynthesis.